The Impact of Social Media on Standard Indonesian Language Competency: A Comparative Analysis Across Age and Educational Levels - Ikah Listiani; Nurhayati Djahadah; Nadia Putri Fatimah (WISE Pendidikan Indonesia, 2023)
The rapid proliferation of social media has significantly influenced the use of the Indonesian language, particularly in the erosion of standard language norms. This study investigates the impact of social media on the usage of standard Indonesian across various age groups and educational levels. Using a mixed-methods approach, data were collected through content observation on popular platforms such as Instagram, Twitter, and Facebook, complemented by in-depth interviews and a comprehensive literature review. The findings reveal a notable shift towards informal language use, characterized by slang, acronyms, and loanwords from English, particularly among younger and less-educated users. This research identifies a negative correlation between the frequency of social media usage and adherence to standard language rules, with significant variations observed across different demographics. The study also proposes strategic interventions, such as digital literacy programs, to preserve and promote the use of standard Indonesian in the digital era. These insights contribute to understanding the evolving dynamics of language in the context of social media and provide a foundation for formulating relevant language policies and educational strategies in Indonesia.